Pembelajaran Kalam dengan Metode Quantum Learning di MA Ibnu Sina Pasuruan - Mishbahuddin, Mohamad (Hidmah : Jurnal Penelitian dan Pengabdian Masyarakat, 2024)
This study evaluates the implementation of the workshop "Kalam Learning with Quantum Learning Method" at MA Ibnu Sina Pasuruan. The main purpose of this activity is to improve students' motivation and speaking skills in Arabic (maharah kalam). The workshop lasted for one day and involved various parties who contributed to creating a fun and interactive learning atmosphere. The results of the study show that the Quantum Learning method has succeeded in increasing the enthusiasm of students, who previously felt that learning Arabic was monotonous. Students show active participation and high enthusiasm during activities, as well as being able to complete projects well. The school gave a positive response, considering that this activity was very useful in improving students' speaking skills. This study concludes that the application of the Quantum Learning method can have a positive impact on learning Arabic, and recommends that similar activities be held regularly to continue to improve students' abilities. Thus, this workshop is not only beneficial for students, but also contributes to the development of more effective learning methods in other educational institutions.